Hybrid photocathode based on a Ni molecular catalyst and Sb2Se3 for solar H2 production. Issue 7 (4th January 2023) - Garcia-Osorio, D. Alicia; Shalvey, Thomas P.; Banerji, Liam; Saeed, Khezar; Neri, Gaia; Phillips, Laurie J.; Hutter, Oliver S.; Casadevall, Carla; Antón-García, Daniel; Reisner, Erwin; Major, Jonathan D; Cowan, Alexander J
Abstract : Here we demonstrate the feasibility of high efficiency Sb2 Se3 photocathodes for hydrogen evolution using precious metal free Ni cocatalysts. Abstract : We report a H2 evolving hybrid photocathode based on Sb2 Se3 and a precious metal free molecular catalyst. Through the use of a high surface area TiO2 scaffold, we successfully increased the Ni molecular catalyst loading from 7.08 ± 0.43 to 45.76 ± 0.81 nmol cm −2, achieving photocurrents of 1.3 mA cm −2 at 0 V vs. RHE, which is 81-fold higher than the device without the TiO2 mesoporous layer.